2017
DOI: 10.1002/gj.3072
|View full text |Cite
|
Sign up to set email alerts
|

Burial and preservation of a fossil forest on an early Permian (Asselian) volcano (Merangin River, Sumatra, Indonesia)

Abstract: The Early Permian (Asselian) Mengkarang Formation of the western Jambi Province, Sumatra, is well exposed in the valley of the Merangin River. No consensus regarding the depositional environment of this section had been reached hitherto. This section preserves abundant evidence of a Permian forest, named the Merangin Fossil Forest herein, which grew at the foot of an active volcano, where pyroclastic flows often made way and destroyed the vegetation and where epiclastic reworked pyroclastics rapidly entombed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Slightly higher up, the transition from sheets to lenticular beds with uncommon coals is interpreted as indicative of the distal foot of the volcanic slope, where sheets are discontinuous (LA‐4). Tree roots in basalt flows (Matysová et al, in press) display the sinuous tapering shape without secondary roots, also observed for the tree roots in Interval II. Both in Interval II and here, in Interval V, the numerous associated Cordaites leaves suggest that Cordaithantales had colonized the volcano slope.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Slightly higher up, the transition from sheets to lenticular beds with uncommon coals is interpreted as indicative of the distal foot of the volcanic slope, where sheets are discontinuous (LA‐4). Tree roots in basalt flows (Matysová et al, in press) display the sinuous tapering shape without secondary roots, also observed for the tree roots in Interval II. Both in Interval II and here, in Interval V, the numerous associated Cordaites leaves suggest that Cordaithantales had colonized the volcano slope.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, the type of root systems associated to the Agathoxylon , as well as Cordaites leaves (Booi et al, ) and inflorescences, is found in gravity flows. This indicates that both the volcanic slope and its alluvially reworked base (Matysová et al, in press) were vegetated by a Cordaites /fern forest. Such a type of forest was also described by Rößler et al () where Psaronius tree ferns, calamitaleans, medullosan, and Cordaixylon gymnosperms were found in the same horizon.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations